A preliminary survey of the application of Industrialised Building System (IBS)in Kedah and Perlis Malaysian construction industry - Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar; Abdullah, Shardy; Mat Yasin, Fadhil (2007)
Statistic shows that between 1995 to 2020,Malaysia will need a total of 8,850,554 houses, including 4,964,560 units of new housing to cater for an increase in population during this period. In the 7th Malaysia Plan, the country intended to construct about 800,000 units of houses for its population.Indeed, 585,000 units or 73.1% were planned for the low and low medium cost houses. Industrialisation is a process of social and economic change whereby a human society is transformed from a preindustrial to an industrial state. It is a part of wider modernisation process through the technology system and one of the solutions for this increasing housing demand. One such technology is the industrialised building system (IBS).In Malaysia, since 1998, the Construction Industry Development Board (CIDB) has been actively promoting the use of IBS in the local construction industry by deploying large funds for research, developing standards as well as implementing various training and promotional programs. Although the IBS system improves the quality of projects, easier to control, reducing rectification work and lowering the total cost of construction, the trend of IBS usage in Malaysian construction projects are still below the national target.This paper highlights the application of the IBS among developers in Kedah and Perlis areas, the types of system used, and the barriers behind the low usage of IBS among developer companies in those areas.Solutions for encouraging the use of IBS for the construction industry have also been identified.